Integrating Digital Technologies to Enhance ESG Performance: A Focus on Central and Eastern European Countries - Eduard Mădălin Dinu; Cecilia Nicoleta Jurcuț; Delia Anca Gabriela Gligor; Irina Daniela Cișmașu; Alexandru Buglea (Amfiteatru Economic)
Grasping the complex interplay between digital innovation and Environmental, Social, and Governance (ESG) practices is vital for policymakers and businesses seeking to promote sustainable economic growth while complying with global sustainability standards. In this context, our paper analysed the impact of integrating digital technologies – quantified through a component of the Digital Economy and Society Index – on the ESG performance of Central and Eastern European (CEE) countries over the last 11 years. The aim of the research was to emphasise how the demands for sustainability reporting have influenced nonfinancial performance, generating national and organisational changes in CEE countries. Drawing on empirical studies and using panel data modelling techniques, we demonstrated that technological advancements foster operational efficiencies, green innovation, ultimately contributing to enhanced carbon emission efficiency and energy performance. In light of ongoing challenges related to varying regulatory frameworks and capacities, our findings underscored the imperative for cohesive strategies that leverage digital tools to meet sustainability goals. This research enriched the theoretical comprehension of the link between digitalisation and ESG performance while offering practical insights to strengthen the sustainability of CEE countries